1992
DOI: 10.1029/91jd02426
|View full text |Cite
|
Sign up to set email alerts
|

The DECAFE experiments: Overview and meteorology

Abstract: The objective of the Dynamique et Chimie de l'Atmosphère en Forêt Equatoriale (DECAFE) program is to determine the influence of African tropics on atmospheric chemistry. Savannas and forests constitute the main ecosystems in this area. Because of the occurrence of biomass burning during the dry season, savannas of the northern and southern hemispheres are active sources of many constituents which are of interest to atmospheric chemistry. The rain forest, with its important biomass activity is also a source or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 22 publications
2
9
1
1
Order By: Relevance
“…1988, Crill et a/. 1988a, Devol et al 1988, Harriss et al 1988 Fontan et al 1992. The overall results from these missions confirm that tropical wetlands are larger sources of methane than early studies suggested.…”
Section: Downloaded By [] At 16:25 03 January 2015supporting
confidence: 61%
“…1988, Crill et a/. 1988a, Devol et al 1988, Harriss et al 1988 Fontan et al 1992. The overall results from these missions confirm that tropical wetlands are larger sources of methane than early studies suggested.…”
Section: Downloaded By [] At 16:25 03 January 2015supporting
confidence: 61%
“…Broadly, the atmospheric circulation is dominated by a large seasonal shift in the position of the intertropical convergence zone (ITCZ), which is determined by the northeast and southwest trade winds, and the monsoon circulation from the Atlantic (Fontan et al 1992). Broadly, the atmospheric circulation is dominated by a large seasonal shift in the position of the intertropical convergence zone (ITCZ), which is determined by the northeast and southwest trade winds, and the monsoon circulation from the Atlantic (Fontan et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In the lower troposphere, moist air from the Atlantic Ocean (Fontan et al 1992), known as low-level equatorial westerlies (Nicholson and Grist 2003), are associated with the southeasterly trades on the northeastern flank of the Saint Helena (South Atlantic) high. Because of Coriolis forces, the southeasterlies become westerlies when crossing the equator.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise measurements during the dry season have been made around the Ivory Coast as part of TROPOZ (December 1987, January 1991 (Jonquieres et al, 1998) and DECAFE (January 1991) (Delmas et al, 1995), and from Niamey as part of AMMA DABEX (January and February 2006). Other measurements in Central and Southern Africa have also focussed on the dry season when there is widespread biomass burning Delmas et al, 1999;Fontan et al, 1992). Figure 28 shows the flight tracks of most of the AMMA 2006 monsoon chemistry flights made by the BAe-146, the DLR Falcon, the French Falcon and the M55 aircraft between 20 July and 21 August plotted as a function of latitude and altitude and coloured by the O 3 concentration.…”
Section: Saharan Aerosolsmentioning
confidence: 99%